The motion of surface particles for the asteroid 101955 Bennu. (October 2019) - Zhang, Yonglong; Zeng, Xiangyuan; Circi, Christian; Vulpetti, Giovanni
Abstract: The asteroid 101955 Bennu is the target asteroid of the ongoing asteroid sample return mission OSIRIS-REx from NASA. In the mission, the spacecraft is scheduled to rendezvous with Bennu in August 2018. Investigating the dynamics of surface motion can offer guidance for further hopping landers or even sample return missions regarding Bennu or similarly irregular-shaped asteroids. This paper presents the free motion of sample particles on and above the surface of Bennu. The concepts and equations that govern the motion of a particle on and above the surface of an asteroid are briefly introduced. Trajectories of a number of particles' free motion are numerically calculated by considering four scenarios with different restitution coefficients. Initial positions of those particles are all randomly given on the surface of Bennu and their initial velocities are set as zero. The distribution of final locations of those sample particles is summarized and analyzed. Both the gravitational potential and its effective potential on the surface of Bennu are calculated to give a possible reason for the distributing characteristics. Highlights: The free motion tendency of surface particles of Bennu are revealed. The effective potential on the surface of Bennu as a polyhedron is calculated. The reason for the free motion tendency of particles is given.